Traditional medicinal knowledge and practices among the tribal communities of Thakht-e-Sulaiman Hills, Pakistan - Khalid Ahmad; Mushtaq Ahmad; Franz K. Huber; Caroline S. Weckerle (BMC, 2021)
Abstract Background Little is known about the medical material and practices of tribes in the western border areas of Pakistan. The local population has inhabited this remote and isolated area for centuries, and gained medicinal knowledge with personal experiences and knowledge learned from forefathers. Due to the geographical isolation of the communities in the Sulaiman hills of Pakistan and their unique culture, the area is of importance for exploration and assessment. Methods A total of 116 informants were interviewed in five foothill villages and the associated migratory mountain villages during 2010-2012 and 2015. Information was gathered mainly through semi-structured interviews and freelisting. Local diseases were categorized based on symptoms and affected organs. Descriptive statistics were used for data analysis. Results Depending on the type of illness, typically a pulse diagnoser or a religious specialist is consulted. Medicinal plant knowledge and use is mostly known and advised by elders within the family. A total of 44 plant species from 32 families (588 use reports), 7 animal species and 6 minerals and other sources (384 use reports) were documented as materia medica. Among the plants, the Lamiaceae is the most dominantly used plant family, followed by Pinaceae. The most frequently reported single species was Teucrium stocksianum. The most often mentioned diseases and treatments fall into the categories of gastrointestinal, ritual, and musculoskeletal diseases. The use of goat and sheep skin as medicine was pivotal in the local medicinal system. Remedies from animal parts and other biological and non-biological sources were mainly used for musculoskeletal ailments and ritual treatments. Overall, people rely on both traditional and biomedical medication and treatments and combination of these systems. Conclusion This paper provides insight into the pluralistic medication system of rural communities of northwest Pakistan. It highlights the materia medica most commonly in use. A considerable part of the documented materia medica and local practices is part of an oral tradition and cannot be found in written sources or scientific articles. The gaining of new medicinal knowledge in the area was the good sign of continuation of traditional medicinal practices.